Photoelectron Spectroscopy for Lithium Battery Interface Studies. Issue 2 (14th November 2015) - Philippe, B.; Hahlin, M.; Edström, K.; Gustafsson, T.; Siegbahn, H.; Rensmo, H.
Abstract : Photoelectron spectroscopy (PES) has become an important tool for investigating Li-ion battery materials, in particular for analyzing interfacial structures and reactions. Since the methodology was introduced in the battery research area, PES has undergone a dramatic development regarding photon sources, sample handling and electron energy analyzers. This includes the possibility to use synchrotron radiation with increased intensity and the possibility to vary the photon energy. The aim of the present paper is to describe how PES can be used to investigate battery interfaces and specifically highlight how synchrotron based PES has been implemented to address different questions useful for the development of the Li-ion batteries. We also present some recent developments of the techniques, which have the potential to further push the limits for the use of photoelectron spectroscopy in battery research.